2013
DOI: 10.4088/jcp.12m07789
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response, Symptom Remission, and Wellness in Obsessive-Compulsive Disorder

Abstract: Objective Obsessive-compulsive disorder (OCD) is defined both by intrusive, unwanted thoughts, images or impulses and by repetitive behavioral or mental acts that are often performed to try to alleviate anxiety. The ultimate goal of treatment for OCD is to reduce the symptoms, as well as help patients achieve “wellness”, however currently there are no widely accepted, empirically supported criteria for determining wellness in OCD. Method Building on previous research, the current study pooled data from four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(144 citation statements)
references
References 33 publications
6
138
0
Order By: Relevance
“…(3) The severity of participants' symptoms was at least moderate, as evidenced by the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) total score of 16 (Farris et al, 2013;Goodman et al, 1989a,b); and (5) All had capacity to give written informed consent.…”
Section: Settings and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The severity of participants' symptoms was at least moderate, as evidenced by the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) total score of 16 (Farris et al, 2013;Goodman et al, 1989a,b); and (5) All had capacity to give written informed consent.…”
Section: Settings and Participantsmentioning
confidence: 99%
“…The secondary outcomes were clinical response and remission. As previously described (Farris et al, 2013), a clinical response was defined as a ≥35% reduction at endpoint from baseline on Y-BOCS total score.…”
Section: Treatment Outcome Measuresmentioning
confidence: 99%
“…4,6 Tolin et al 7 employed signal detection analysis methodology with the results from the clinical global impression scale as reference and concluded that a Y-BOCS reduction criterion of 30% was optimal for determining improvement, whereas a 40% to 50% reduction criterion was appropriate for predicting a condition of mild illness as the outcome. Similarly, Farris et al 8 showed that the widely used 35% reduction criterion of response based on Y-BOCS scores does not represent improvement as reliably as other measures such as clinical global impression, quality of life and social adaptation. However, instead of reestablishing the percent reduction threshold, the authors proposed the use of Y-BOCS cut-off of 14 points to define remission and the use of additional instruments to compose a criterion of wellness.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In previous studies, the threshold of Y-BOCS percent reduction from baseline had already been questioned. 7,8 However, by simply reestablishing the threshold we do not solve the problem of misrepresentation of a doubled score (i.e., the summing up of subscales that are highly correlated) and do not correct for a more realistic expectation of improvement.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Some pharmacological studies have defined symptom response as a 25% reduction in the Y-BOCS, whereas others have defined symptom response as a 35% reduction. In a study designed to determine which definition is most appropriate by comparing Y-BOCS reduction with Clinical Global Impression Scale scores, Farris et al [6] conclude that a reduction of greater than or equal to 35% in Y-BOCS scores is the best definition of treatment response in OCD.…”
Section: Treatment Responsementioning
confidence: 99%